A small wins framework to overcome the evaluation paradox of governing wicked problems. Issue 2 (3rd April 2019) - Termeer, Catrien J.A.M.; Dewulf, Art
ABSTRACT: The evaluation of policy strategies to tackle wicked policy problems inevitably involves a paradox of trying to judge solutions for problems that have no solutions and for which additional efforts might increase the chances of finding better responses. This paper analyzes how the concept of small wins can contribute to evaluating progress in wicked problem areas in a way that energizes a variety of stakeholders instead of paralyzing them and embraces complexity instead of reverting to taming and overestimation. It presents a small wins evaluation framework that is rooted in the underlying policy perspective of making progress through accumulating small wins. It comprises three steps: 1) identifying and valuing small wins; 2) analyzing whether the right propelling mechanisms are activated so as to accumulate into transformative change; 3) organizing that results feed back into the policy process to activate new small wins. This framework will inevitably clash with unrealistic expectations of addressing wicked problems rapidly, radically and comprehensively.